DESIGNING AND ASSESING AN ISLAMIC ENTREPRENEURSHIP EDUCATION MODEL FOR ISLAMIC HIGHER EDUCATION (IHE) - Lailatussaadah Lailatussaadah; Asyraf Isyraqi Bin Jamil; Fakhrul Adabi Bin Abdul Kadir (Islam Futura, 2023)
The implementation of entrepreneurship course can be carried out by integrating the tridharma of higher education (the threefold missions of higher education) simultaneously in learning, for which a guideline is needed for its implementation. This study aims to design and assess the Islamic Entrepreneurship Education (IEE) model in the tridharma in Islamic Religious Universities (PTKI) in Aceh. This research was conducted through Design-Based Research (DBR) involving 3 experts and 6 lecturers. The research instrument used was a questionnaire which was analyzed statistically descriptively, while the qualitative data used interviews and were analyzed with an interactive model. The results of the design of the IEE model has produced three aspects along with four elements for the dimensions of education and teaching, research, and community service. These three aspects are inter-curricular activities, co-curricular activities, and extra-curricular activities, while the four elements are the objectives of implementing entrepreneurship education learning activities, entrepreneurial learning materials/content, using entrepreneurship learning methods, and implementing evaluations of entrepreneurship learning. The design of this model has the description for the implementation procedure. This design of IEE model can be used by lecturers as a model for implementing IEE in Islamic Religious Universities.